Analisis Yuridis Saksi Testimonium De auditu dalam PerkaraItsbat Nikah di Mahkamah Syar’iyah Bireuen - Tasrizal; Muhammad Rudi Syahputra; Alia Rahma (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study analyzes the legal position of testimonium de auditu witnesses in itsbat nikah cases at the Mahkamah Syar’iyah Bireuen. Normatively, Indonesian civil procedure law through Article 171 HIR and Article 1907 of the Civil Code requires witnesses to provide testimony based on direct knowledge, thereby rejecting hearsay as valid evidence. However, in practice, especially in itsbat nikah cases where direct witnesses are often unavailable, judges frequently face demands to consider such testimony. Using a normative-empirical approach, this research combines legal analysis of statutory provisions and jurisprudence with field data from case studies and interviews with judges. The findings reveal that the Mahkamah Syar’iyah Bireuen consistently does not treat testimonium de auditu as primary evidence, but only as complementary proof that must be supported by other evidence such as documents or direct witness testimony. The implication is a balance between legal certainty and substantive justice, ensuring protection for women and children from unregistered marriages while maintaining procedural safeguards.